Establishing a set of macroeconomic factors explaining variation over time of performance in business sectors - Dzikevičius, Audrius; Šaranda, Svetlana (Business: Theory and Practice, 2016)
With increasing competitiveness of companies and business sectors in the domestic markets of Lithuania, economic units are frequently confronted with the lack of methods for more detailed analysis of external factors explaining the variation over time of corporate financial indicators. The analysis or forecasting of financial indicators is usually linked with the development of a stock market or undertaken to estimate the probability of bankruptcy. However, there is a lack of studies aimed at identifying links between macroeconomic factors and financial performance indicators and explaining their variation over time. To serve that purpose, the factors of the macroeconomic environment that are most significant for certain economic activities have been identified and analysed to enable explaining the variation over time patterns of corporate financial indicators. The analysis covers economic performance, i.e. financial performance indicators and their links with macroeconomic factors, in 89 business sectors of Lithuania at a three-digit level of NACE 2 ed. The findings of the research indicate that the unemployment level in the country, the volume of export and import and the GDP are the most important macroeconomic factors that can be used to forecast different profitability, financial leverage, liquidity and other financial performance indicators of individual business sectors or companies. The research has not unfolded any significant differences between business sectors therefore the above factors are considered generic macroeconomic factors enabling to explain financial performance indicators of the 89 business sectors. Hence, special attention has to be paid to identifying and analysing specific factors and assessing the causal link. When established, the set of such factors provides a framework for building of a model to forecast business sector financial indicators.